2017
DOI: 10.1002/14651858.cd011859.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Personalised asthma action plans for adults with asthma

Abstract: Analysis of available studies was limited by variable reporting of primary and secondary outcomes; therefore, it is difficult to draw firm conclusions related to the effectiveness of PAAPs in the management of adult asthma. We found no evidence from randomised controlled trials of additional benefit or harm associated with use of PAAP versus no PAAP, or PAAP plus education versus education alone, but we considered the quality of the evidence to be low or very low, meaning that we cannot be confident in the mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 76 publications
1
29
0
Order By: Relevance
“…Although personalised written action plans help to improve asthma control in adults and children with asthma, their impact on overall HRQoL is small (SMD = 0.18; 95% CI, 0.05-0.30). 47,48 Mental health problems, obesity and physical inactivity are associated with substantial deficits in HRQoL; therefore, addressing these with evidence-based approaches is also warranted. 30,49,50 Importantly, non-pharmacological interventions may have an impact across multiple quality of life domains, risk factors and comorbidities.…”
Section: Non-pharmacological Interventions and Health-related Qualitymentioning
confidence: 99%
“…Although personalised written action plans help to improve asthma control in adults and children with asthma, their impact on overall HRQoL is small (SMD = 0.18; 95% CI, 0.05-0.30). 47,48 Mental health problems, obesity and physical inactivity are associated with substantial deficits in HRQoL; therefore, addressing these with evidence-based approaches is also warranted. 30,49,50 Importantly, non-pharmacological interventions may have an impact across multiple quality of life domains, risk factors and comorbidities.…”
Section: Non-pharmacological Interventions and Health-related Qualitymentioning
confidence: 99%
“…As of May 2018, a total of 22 systematic reviews examining one or more learning focused interventions for people with respiratory‐related conditions compared to usual care had been published in the Cochrane Database of Systematic Reviews . The patient population groups include adults with asthma (11 reviews), COPD (3 reviews), smoking cessation (2 reviews), cystic fibrosis (1 review), bronchiectasis (1 review), acute upper respiratory tract infections (1 review), lung cancer (1 review), obstructive sleep apnoea (1 review) and tuberculosis (1 review) . The reviews reported two main categories of educational interventions: (i) didactic‐focused teaching for knowledge and (ii) learning experiences for developing self‐management strategies.…”
Section: Impact Of Education Within Prmentioning
confidence: 99%
“…Significant positive impact on healthcare use and quality of life has been demonstrated with interventions to improve self‐management compared to usual care in chronic respiratory conditions . As such, the literature on self‐management interventions provides guidance for PR programmes on opportunities for enhancement of programmes and/or the addition of features to PR that support patients to also engage in a tailored self‐management intervention.…”
Section: Self‐management Interventions and Prmentioning
confidence: 99%
“…It is also critical that clinicians deliver education on recognition of early signs and symptoms of worsening asthma . Individuals should be provided with and instructed on use of a home peak flow meter, and a written asthma action plan that includes information on when to seek medical care should be developed in collaboration with the client . Peak flow meters measure how much air an individual can expel out of the lungs in one fast blast of breath .…”
Section: Client Educationmentioning
confidence: 99%
“…Although studies have not confirmed that a personalized, written asthma action plan improves asthma outcomes compared with verbal education from the clinician alone, asthma experts recommend the use of asthma action plans. Many institutions have adopted asthma plans, and templates can be found on several internet sites …”
Section: Client Educationmentioning
confidence: 99%